Adsorption of Malachite Green in Aqueous Solution by the Thermally Modified Rice Husk - Sriuttha, Manop (KKU Science Journal, 2014)
The thermally modified rice husk (TMRH) was evaluated as a low cost adsorbent for adsorption of toxic dye, malachite green, from aqueous solution in batch adsorption experiments. The effect of initial dye concentration and contact time of malachite green on TMRH adsorption was studied. The optimal time for malachite adsorption was reached in 1 h. Langmuir and Freundlich isotherms were used to investigate the equilibrium data. The Langmuir isotherm model showed good fit to the equilibrium adsorption data, showing a monolayer adsorption. The maximum monolayer adsorption capacity was found to be 50 mg g-1. The result indicated that TMRH was an adsorbent for the removal of malachite green from aqueous solution.